The mTORC1‐eIF4F axis controls paused pluripotency. (6th December 2021) - Xu, Xueting; Ahmed, Tanveer; Wang, Lulu; Cao, Xintao; Zhang, Zeyu; Wang, Ming; Lv, Yuan; Kanwal, Shahzina; Tariq, Muqddas; Lin, Runxia; Zhang, Hui; Huang, Yinghua; et al.
Abstract: Mouse embryonic stem cells (mESCs) can self‐renew indefinitely and maintain pluripotency. Inhibition of mechanistic target of rapamycin (mTOR) by the kinase inhibitor INK128 is known to induce paused pluripotency in mESCs cultured with traditional serum/LIF medium (SL), but the underlying mechanisms remain unclear. In this study, we demonstrate that mTOR complex 1 (mTORC1) but not complex 2 (mTORC2) mediates mTOR inhibition‐induced paused pluripotency in cells grown in both SL and 2iL medium (GSK3 and MEK inhibitors and LIF). We also show that mTORC1 regulates self‐renewal in both conditions mainly through eIF4F‐mediated translation initiation that targets mRNAs of both cytosolic and mitochondrial ribosome subunits. Moreover, inhibition of mitochondrial translation is sufficient to induce paused pluripotency. Interestingly, eIF4F also regulates maintenance of pluripotency in an mTORC1‐independent but MEK/ERK‐dependent manner in SL, indicating that translation of pluripotency genes is controlled differently in SL and 2iL. Our study reveals a detailed picture of how mTOR governs self‐renewal in mESCs and uncovers a context‐dependent function of eIF4F in pluripotency regulation. Synopsis: The mTORC1‐eIF4F axis controls mouse ESC self‐renewal through translation initiation. eIF4F regulates pluripotency in mouse ESCs cultured in serum+LIF. mTORC1 but not mTORC2 controls mouse ESC self‐renewal. Translation initiation complex eIF4F mediates mTORC1's role in mouse ESC self‐renewal. eIF4F coordinates both cytosolic and mitochondrial translation in mouse ESCs. eIF4F regulates pluripotency of mESCs grown in SL in an mTORC1‐independent but MEK/ERK‐dependent manner. Abstract : mTORC1‐eIF4F axis controls mouse ESC self‐renewal through translation initiation. eIF4F regulates pluripotency in mouse ESCs cultured in serum+LIF.